Investigation on core-fucosylated prostate-specific antigen as a refined biomarker for differentiation of benign prostate hyperplasia and prostate cancer of different aggressiveness - Robert Lang; Vinzent Rolny; Andreas Leinenbach; Johann Karl; Magdalena Swiatek-de Lange; Uwe Kobold; Mark Schrader; Hans Krause; Markus Mueller; Michael Vogeser (Tumor Biology)
Prostate cancer represents a major cause of cancer death in men worldwide. Novel non-invasive methods are still required for differentiation of non-aggressive from aggressive tumors. Recently, changes in prostate-specific antigen glycosylation pattern, such as core-fucosylation, have been described in prostate cancer. The objective of this study was to evaluate whether the core-fucosylation determinant of serum prostate-specific antigen may serve as refined marker for differentiation between benign prostate hyperplasia and prostate cancer or identification of aggressive prostate cancer. A previously developed liquid chromatography–mass spectrometry/mass spectrometry–based strategy was used for multiplex analysis of core-fucosylated prostate-specific antigen (fuc-PSA) and total prostate-specific antigen levels in sera from 50 benign prostate hyperplasia and 100 prostate cancer patients of different aggressiveness (Gleason scores, 5–10) covering the critical gray area (2–10 ng/mL). For identification of aggressive prostate cancer, the ratio of fuc-PSA to total prostate-specific antigen (%-fuc-PSA) yielded a 5%–8% increase in the area under the curve (0.60) compared to the currently used total prostate-specific antigen (area under the curve = 0.52) and %-free prostate-specific antigen (area under the curve = 0.55) tests. However, our data showed that aggressive prostate cancer (Gleason score > 6) and non-aggressive prostate cancer (Gleason score ≤ 6) could not significantly (p-value = 0.08) be differentiated by usage of %-fuc-PSA. In addition, both non-standardized fuc-PSA and standardized %-fuc-PSA had no diagnostic value for differentiation of benign prostate hyperplasia from prostate cancer. The %-fuc-PSA serum levels could not improve the differentiation of non-aggressive and aggressive prostate cancer compared to conventional diagnostic prostate cancer markers. Still, it is unclear whether these limitations come from the biomarker, the used patient cohort, or the imprecision of the applied method itself. Therefore, %-fuc-PSA should be further investigated, especially by more precise methods whether it could be clinically used in prostate cancer diagnosis.